IMPLEMENTATION OF EARLY CHILDHOOD REGIONAL LANGUAGE (SUNDANESE) LEARNING THROUGH MOVEMENT AND SONG METHODS - YOSFIANI, NELY; NURHAYATI, SRI (HIKMAH: JURNAL PENDIDIKAN AGAMA ISLAM, 2023)
The preservation of regional languages and cultural identities is of paramount importance, particularly in early childhood education. This research aims to investigate the implementation of Sundanese language learning through a dynamic blend of movement and song methods at TK Kemala Bhayangkari 37 in Bandung.  The study conducted through a qualitative research approach with descriptive method involving in depth interviews and classroom observations, and documentation study techniques. The informants include 2 parents, 2 ECCE teachers, and 10 students at TK Kemala Bhayangkari 37 Bandung. The results of this study highlight the important impact of the movement and song-based instructional approach on the language proficiency and cultural sensitivity of young students. Educators, serving as key individuals in this educational process, assume a crucial role in establishing a stimulating and efficacious milieu for learning. The active participation of parents additionally supports the incorporation of regional languages into everyday activities. The present study is a significant resource for educators and policymakers who are committed to advancing the preservation and development of regional languages and cultural identities within the context of early childhood education.